Bimbingan Konseling Kecerdasan Intrapersonal Siswa SDIT Kayyatal Jihaaz Kecamatan Tanjungsari Sumedang - Syamsul Maarief; Supian Munawar; Ulfah Ulfah; Akhmad Roziqin (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Intrapersonal intelligence is a fundamental pillar in the structure of multiple intelligences that determines an individual’s capacity to map, understand, and regulate their inner landscape, encompassing emotional awareness, existential reflection, and self-control. Within the realm of Islamic education, this psychological dimension is rooted in the spiritual doctrine of tazkiyatun nafs (purification of the soul) and the methodology of muhasabah (critical introspection). This article aims to comprehensively examine the theoretical foundations, conceptual frameworks, and practical dynamics of implementing intrapersonal intelligence within an integrated Islamic elementary education institution. Utilizing a qualitative approach with an intrinsic case study design, this research explores the empirical reality at SDIT Kayyatal Jihaaz, Tanjungsari, Sumedang Regency. Data were gathered through participant observation, in-depth interviews, and curriculum documentation reviews. The research findings reveal a significant psychosocial polarization in the field; on one hand, there is a group of learners whose intrapersonal capacity has developed optimally, but on the other hand, behavioral pathologies are observed, including emotional regulation deficits, indisciplinary actions, verbal and non-verbal bullying, peer conflicts, and high absenteeism rates that ultimately culminate in school transfers. This study recommends the necessity of structural reforms through the provision of professional guidance and counseling personnel, the enhancement of teacher pedagogical competence based on deep learning, and the integration of a holistic reflective-spiritual learning model.